Factors Predicting Quality of Life among Elderly People at Geriatric Homes in Baghdad City - Khamis, Shahad H.; Mohammed, Zahid J. (Iraqi National Journal of Nursing Specialties, 2024)
Objective(s): This study aimed to assess quality of life among elderly in geriatric homes and its influencing factors.Methods: A descriptive cross-sectional study conducted in a geriatric home in Baghdad for the period from November 1st, 2022 to March 1st, 2023, on a sample of (139) elderly people. A validated WHOQOL-BREF questionnaire was used with a total number of 28 items for quality-of-life assessment. Data were collected using interviews and analyzed by applying descriptive and inferential statistical analysis.Results: The results indicate that the average age of the participants was 72.15 (± 2.39) years, more than half of the participants were males (58.3%), the monthly income was less than 300 thousand Iraqi dinars (45.3%), more than half of them have sons (59.7%). The results showed that (55.4%) of the elderly expressed a low quality of life. The study indicated that participants age, sex, marital status, monthly income, educational level, who have sons, length of stay in a geriatric home, and associated chronic diseases are all factors that predict quality of life among the elderly (p